Accessibility of technology in crisis counseling services: facilitating students with traumatic experiences - Pasaribu, Berlima; Hafina, Anne (Universitas Islam Negeri Raden Intan Lampung, 2024)
The purpose of this study was to identify the availability of digital-based crisis counselling services in twenty schools in Medan city. The Integration of technology in crisis counselling services is important to support students experiencing trauma such as bullying, violence, parental divorce, academic failure and others so that they can overcome post-traumatic stress and promote mental wellbeing. The research method used a quantitative approach with a descriptive survey design. The participants were Guidance and Counselling Teachers from twenty high schools in Medan city. The results showed that despite the availability of counselling services, there was no school that had technology-based accessibility for students with trauma experiences. The implication of this study is therefore for schools to develop technology-based counselling services to help students with traumatic experiences.